2005
DOI: 10.1074/jbc.m414391200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Lesion-specific Co-localization of the Mre11/Rad50/Nbs1 (MRN) Complex and Replication Protein A (RPA) to Repair Foci

Abstract: The DNA damage response, triggered by DNA replication stress or DNA damage, involves the activation of DNA repair and cell cycle regulatory proteins including the MRN (Mre11, Rad50, and Nbs1) complex and replication protein A (RPA). The induction of replication stress by hydroxyurea (HU) or DNA damage by camptothecin (CAMPT), etoposide (ETOP), or mitomycin C (MMC) led to the formation of nuclear foci containing phosphorylated Nbs1. HU and CAMPT treatment also led to the formation of RPA foci that co-localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 71 publications
2
52
0
Order By: Relevance
“…65 We previously reported that RPA and MRN complex co-localization is dependent on the type of damage present. 21 We observed that treatment with ETOP led to cells containing either RPA or phospho-Nbs1 foci, but not both. In the companion paper, we demonstrate that RPA is however required for the formation of the MRN foci.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…65 We previously reported that RPA and MRN complex co-localization is dependent on the type of damage present. 21 We observed that treatment with ETOP led to cells containing either RPA or phospho-Nbs1 foci, but not both. In the companion paper, we demonstrate that RPA is however required for the formation of the MRN foci.…”
Section: Introductionmentioning
confidence: 80%
“…4,[10][11][12][13][14][15][16][17][18][19][20][21] RPA is also hyperphosphorylated (particularly the p34 subunit) following DNA damage and replicative stress. [20][21][22][23] which is hypothesized to function as a "switch" to direct RPA activity from DNA replication to DNA repair. 9,24,25 The MRN complex is composed of Mre11, Rad50 and Nbs1.…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon is evident in response to stalled replication forks. Nuclear co-localization of Mre11, Rad50 and Nbs1 with other DNA damage response molecules, phosphorylated ATM and H2AX, increases in response to gemcitabine, ara-C, troxacitabine and hydroxyurea (Wang et al, 2000;Mirzoeva and Petrini, 2003;Robison et al, 2005;Ewald et al, 2008).…”
Section: Dna Repair and Drug Resistancementioning
confidence: 99%
“…What is the biological significance underlying the specific binding of ScMre11 to intermediates of recombination and repair? A large body of evidence supports the view that the Mre11 complex plays a key role in the process of DNA replication (65)(66)(67)(68)(69)(70); however, the mechanism is less well characterized. The observation that Mre11 exhibits striking selectivity toward replication fork and flayed duplex is consistent with its demonstrated role during "normal" replication or under conditions of replicative stress (70).…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, recent studies have shown that Mre11 complex, specifically its nuclease activity, plays an essential role in processing of the stalled replication forks, thereby helping to maintain genome integrity during replication stress (65)(66)(67)(68)(69)(70). To understand the mechanism of processing of stalled replication forks and other intermediates by MRX complex better, we considered whether ScMre11 could unwind replication and recombination intermediates, such as the Holliday junction and flayed duplex substrates.…”
Section: Scmre11 Binds To Dsb Ends and Promotes End Bridging Between mentioning
confidence: 99%